Consumer Self-Confidence and Electronic Word-of-Mouth : A Step Towards the Understanding of Viral Marketing - Geborek Lundberg, David; Lind, Karl (2016)
Social media is a continuously rising phenomena among individual consumers. Consequently, companies are to a large extent utilizing social networks in their marketing strategies. The social nature of social media enables successfully incorporated marketing messages to reach global audiences in a short period of time, normally referred to as viral marketing. There is currently a gap in the theoretical understanding regarding why some messages go viral. However, theory indicates that it is based on consumers’ interaction, or electronic Word-Of-Mouth behavior, through online social platforms. The purpose of this research is to enhance the understanding of what motivates individuals’ intention to interact through social media platforms. This is done through an exploration of how individuals perceived Consumer Self-Confidence, elucidated through six sub dimensions, explains their perceived electronic Word-Of-Mouth behavior. The research is of a quantitative explanatory nature and primary data was collected through an online questionnaire distributed amongst program students at Luleå University of Technology. A total of 292 complete answers were collected and analyzed using statistical techniques. The results suggest that Consideration-Set formation, Social Outcome and Personal Outcome decision making are the most prominent dimensions of Consumer Self-Confidence in regards of explaining perceived electronic Word-Of-Mouth behavior in Social Networking Sites. Validerat; 20160615 (global_studentproject_submitter)